RECRUITMENT FOR THE PROFESSION. - Nissley, Warren W. (The Accounting Review, 1947)
Abstract There is no doubt but that the importance of the services which professional accountants are capable of rendering to the community is not fully appreciated in the United States. While there has been substantial improvement in this connection during the last twenty years, much remains to be done. The paper argues that one important reason why accountants are not better recognized is that they have not been rendering all the public service of which they are capable. In particular, they have as a profession, and as individual members of it, been backward in advising the public of facts of which our practitioners should be more cognizant than any other segment of the population. The remarks up to this point relate to the kind of additional activities which might be undertaken to increase the accountant's standing in the community-and hence their prestige with young men about to choose a career. This sort of thing can help accounting only over the long future. For the immediate objective, it is necessary to give additional publicity to the importance of the work which accountants now do. It is particularly necessary that it should be done in terms that will add some atmosphere of glamour to the work of the profession.